2019
DOI: 10.1111/bjh.16157
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic use of regulatory T cells for graft‐versus‐host disease

Abstract: Regulatory T cells (Treg cells) represent a CD4 + T-cell lineage that plays a critical role in restraining immune responses to self and foreign antigens and associated inflammation. Due to the suppressive function of Treg cells, inhibition or ablation of these cells can be used to boost the immunity against malignant cells. On the other hand, augmenting the activity of Treg cells can be employed for the treatment of inflammatory or autoimmune diseases and allogeneic conflicts associated with transplantation. G… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
33
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(33 citation statements)
references
References 108 publications
(136 reference statements)
0
33
0
Order By: Relevance
“…They have shown positive results in preclinical trials and their ability to ameliorate GVHD is under investigation. However, this approach requires standardization of Treg expansion methods and doses [39,40]. Inducible Tregs can readily be generated, but controversial preclinical ndings and phenotype instability have hampered their translation to the clinic [18].…”
Section: Discussionmentioning
confidence: 99%
“…They have shown positive results in preclinical trials and their ability to ameliorate GVHD is under investigation. However, this approach requires standardization of Treg expansion methods and doses [39,40]. Inducible Tregs can readily be generated, but controversial preclinical ndings and phenotype instability have hampered their translation to the clinic [18].…”
Section: Discussionmentioning
confidence: 99%
“…Treg cells are negatively associated with the development of GvHD and other inflammatory diseases including arthritis, irritable bowel syndrome, atopic dermatitis, and psoriasis [103,104]. In mouse models of GvHD, both natural and induced Treg cells suppress the proliferation of conventional T cells, thereby preventing GvHD while preserving the GvL effect [105,106].…”
Section: Effect Of Hdac Inhibitors On Donor T Cell Activation and Difmentioning
confidence: 99%
“…Early clinical trials with iT reg infusion in patients have shown promising results for aGVHD prevention (178)(179)(180), [reviewed in (164)]. Nevertheless, the major problem with the clinical transfer of T reg is the difficulty of reaching a sufficient number of T reg with good purity to infuse and of ensuring that the transferred cells persist and retain their tolerogenic properties in the inflammatory context of aGVHD (181).…”
Section: Strategies Aimed At Promoting Immune Tolerancementioning
confidence: 99%